2016
DOI: 10.1016/j.ymgme.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

221 newborn-screened neonates with medium-chain acyl-coenzyme A dehydrogenase deficiency: Findings from the Inborn Errors of Metabolism Collaborative

Abstract: INTRODUCTION There is limited understanding of relationships between genotype, phenotype and other conditions contributing to health in neonates with medium-chain acyl-coenzyme A dehydrogenase deficiency (MCADD) identified through newborn screening. METHODS Retrospective analysis of comprehensive data from a cohort of 221 newborn-screened subjects identified as affected with MCADD in the Inborn Errors of Metabolism – Information System (IBEM-IS), a long term follow-up database of the Inborn Errors of Metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…These protocols cover a selected panel of diseases by quantifying the metabolites in a disease pathway and metabolite levels are then compared to the range of healthy (normal) metabolic concentrations [66,119,120]. For some diseases, metabolite measurements are assembled into panels [121,122]. The most commonly screened panels of IEMs are using markers of amino acids, fatty acid oxidation, and organic acid metabolism disorders [123,124,125].…”
Section: Targeted Metabolomics In the Screening And Diagnosis Of mentioning
confidence: 99%
“…These protocols cover a selected panel of diseases by quantifying the metabolites in a disease pathway and metabolite levels are then compared to the range of healthy (normal) metabolic concentrations [66,119,120]. For some diseases, metabolite measurements are assembled into panels [121,122]. The most commonly screened panels of IEMs are using markers of amino acids, fatty acid oxidation, and organic acid metabolism disorders [123,124,125].…”
Section: Targeted Metabolomics In the Screening And Diagnosis Of mentioning
confidence: 99%
“…According to previous reports, each nation or ethic group shows a unique spectrum of ACADM gene mutations. The c.985A > G was the most common mutation for MCAD deficiency in many countries and regions, including the United Sates (Bentler et al, 2016), Germany (Maier et al, 2005), Denmark (Andresen et al, 2001), Portugal (Ventura et al, 2014; Janeiro et al, 2019), Caucasia (Grosse et al, 2006), and other European countries (Tanaka et al, 1997). However, the c.985A > G is rare in Asian patients with MCAD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined LTFU data to describe the clinical outcomes associated with expanded NBS using tandem mass spectrometry, including inborn errors of metabolism, 14 mitochondrial fatty acid beta-oxidation defects, 15 VLCAD, 16,17 malonic acidemia, 18 MCAD, 19 and urea cycle disorders. 20 Using LTFU data collected in California, Gallant 21 described the biochemical, molecular, and clinical characteristics of children with short-chain acyl CoA dehydrogenase deficiency (listed as a secondary RUSP disorder) and concluded that this disorder was not associated with significant morbidity or mortality in newborns followed through age 5.…”
Section: Discussionmentioning
confidence: 99%